Новые данные о метацеркариях Halipegus ovocaudatus Vulp., 1858 (Trematoda, Halipegidae) - Павлюк, Р.С. (Вестник зоологии, 1973)
When dissecting 400 larvae and 13 520 adult dragon-flies of 57 species caught in the suburbs of 120 settlements of the western regions of the Ukraine, in 125 dragon-flies froni the water bodies of suburbs of 46 settlements metacercariae of trematode Halipegus coocaudatus V u l p. are found. Invasion extensity is about 0.9, intensity 1-11 individuals. Metacercariae are found not in the body cavity (literature data) but in the middle gut of dragon-flies. 17 species of dragon-flies are registered as additional hosts of H. oeocaudo. tus unknown in literature till now. Body sizes of metacercariae are given.